Local Wisdom in Indonesian Language Instruction and Students’ Cultural Literacy: A Qualitative Case Study - Wayan Pageyasa; Andi Saadillah; Rudi Karma (Sakura Digital Nusantara, 2026)
Indonesian language instruction has the potential to connect literacy development with students’ cultural identities. However, the integration of local wisdom into classroom instruction is often constrained by limited learning resources and insufficient instructional planning. This study examined how local wisdom was represented in Indonesian language instruction, how teachers and students perceived the value of culturally relevant materials for cultural literacy, and what institutional conditions supported or constrained their integration. A qualitative case study was conducted at SMPN 2 Kolaka, Southeast Sulawesi. The participants comprised one principal, two Indonesian language teachers, and 64 Grade VIII students involved in six observed lessons. Five students were purposively selected for individual interviews. Data were collected through classroom observations, semi-structured interviews, and document analysis. The data were coded and organized into themes, and the interpretations were strengthened through source and method triangulation. The findings showed that local wisdom had not been systematically integrated into instructional planning or classroom practice. Learning materials were dominated by nationally published textbooks, while locally relevant folklore, traditions, cultural inquiry activities, and community cultural resource persons were used only to a limited extent. The interviewed students were generally more familiar with visible cultural forms than with their underlying meanings, values, and social functions. Teachers considered culturally relevant materials useful for connecting instruction with students’ experiences, but they reported constraints related to preparation time, references, instructional resources, and the absence of structured teaching modules. These findings suggest that strengthening culturally contextualized Indonesian language instruction requires systematic planning, locally relevant materials, collaborative module development, cultural inquiry activities, and sustained institutional support.